The Implementation of Ground Response Analysis to Quantify Liquefaction Potential Index (LPI) in Bengkulu City, Indonesia - Lindung Zalbuin Mase; Muhammad Farid; Nanang Sugianto; Sintia Agustina (Journal of the Civil Engineering Forum, 2020)
Bengkulu City is one of the areas vulnerable to earthquakes in Indonesia and several studies have shown the city experienced a unique phenomenon called liquefaction during the Mw 8.6 Bengkulu-Mentawai Earthquake. This event has initiated a step by step intensive study on earthquake in the area but previous studies are generally limited by the use of site investigation data to empirically analyse liquefaction potential and those that used advance method such as the seismic wave propagation model are rare. This means the level of liquefaction damage in the study area is not totally understood, therefore, this research focused on implementing the ground response analysis to quantify the Liquefaction Potential Index (LPI) using several areas in Bengkulu City in order to determine their vulnerability. The process involved the collection of several site investigation data including boring log and shear wave velocity profile as well as a desk study to determine the geological condition of the observed sites. Moreover, a non-linear seismic ground response analysis was conducted to obtain maximum ground surface acceleration (amax) parameter which was further used to analyse the liquefaction potential in the study area. The results showed several sites have the potential to experience liquefaction during earthquakes. The method applied was considered successful and the results are expected to be implemented for city development. Furthermore, the framework is recommended for adoption in investigating the liquefaction in other areas.